Lagu ABC (Ada Banyak Cara) Karya Trio Bimbo Dalam Analisis Wacana Michel Foucault - Ubaidillah Ubaidillah (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2014)
This paper examines a song criticizing the phenomenon that occurs in the body of the government of Indonesia nowadays. Lyric of a song ABC (Ada Banyak Cara) by Trio Bimbo that becomes the focus of study in this paper is interesting to be studied, considering the Trio Bimbo is famous musicians who focused on religious themes, voicing out his heart in criticizing the government.The discourse theory of Michel Foucault,in which his discourse of language is closely related to who is in power in the region, is used to analyze this song.The result founds that the discourse of language in the ABC song is representation the mercy of the people, in this case represented by Trio Bimbo sound, such as naikkan gaji sendiri, duduk sidang terus mimpi, jaksa hakim wiraswasta, and other discordant expressions that criticize the government. Trio Bimbo does not hesitate to cast his criticism of the government by voicing the discourse of language which is considered as a direct criticism, without the subtle innuendo. If this happens in the Orde Baru era, the discourse of language must be prohibited by the government, because they were in power at that time. However, after the fall of Orde Baru, resime people have the power to create their own linguistic discourse.